2009
DOI: 10.1017/s0022029909004130
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing dairy steers and organically managed dairy cows with synthetic vitamin D3is unnecessary at pasture during exposure to summer sunlight

Abstract: Use of synthetic feed additives, including synthetic vitamin D3 (D3) in the feed for cows and other ruminants, is not consistent with the international principles of organic farming. If dairy farmers wish to produce in accordance with the organic principles, production animals would be left with only their endogenous production of D3 from summer sunlight as a source of D3. To examine the impact of supplemental synthetic D3 from the feed on the D3 status of dairy cattle in organic production in Nordic countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 9 publications
5
25
0
1
Order By: Relevance
“…Although Daniel et al (2004) reported that vitamin A supplementation can stimulate D-9 desaturase activity, leading to higher proportions of C16:1c-9 and C18:1c-9, such effects would not be relevant to this trial because vitamin A content was not affected by vitamin supplementation in either the indoor or outdoor finishing programmes. The difference in plasma 25-OH D 3 between supplemented groups present at the start of the trial (Hymøller et al, 2009) remained at the indoor finishing period slaughter point. However, UV light exposure during the outdoor pasture finishing programme was sufficient to equalise the plasma 25-OH D 3 concentrations between outdoor vitamins A, D 3 and E supplemented and non-supplemented animals.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Although Daniel et al (2004) reported that vitamin A supplementation can stimulate D-9 desaturase activity, leading to higher proportions of C16:1c-9 and C18:1c-9, such effects would not be relevant to this trial because vitamin A content was not affected by vitamin supplementation in either the indoor or outdoor finishing programmes. The difference in plasma 25-OH D 3 between supplemented groups present at the start of the trial (Hymøller et al, 2009) remained at the indoor finishing period slaughter point. However, UV light exposure during the outdoor pasture finishing programme was sufficient to equalise the plasma 25-OH D 3 concentrations between outdoor vitamins A, D 3 and E supplemented and non-supplemented animals.…”
Section: Discussionmentioning
confidence: 91%
“…Animal feeding and housing Swedish Red breed steers from a previous vitamin trial (Hymøller et al, 2009) were divided into vitamin supplemented (n 5 12) and non-supplemented (n 5 15) groups while on pasture before the finishing period. This trial started at the beginning of November when the steers were moved indoors and began the finishing phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations